The active performance factors that influence the success of Bumiputera women entrepreneurs in Selangor / Siti Sarah Safaruddin and Azizan Zainuddin - Safaruddin, Siti Sarah; Zainuddin, Azizan (Universiti Teknologi MARA, 2019)
In the era of globalization, the role of women in the business sector in Malaysia are increasingly being recognized, as the Female Labor Participation Rate (FLPR) is escalating year by year. The growth is undeniably helps towards the nation’s development, and also creates vast opportunities for women to be actively involved in economic activities. Consequently, an increase in the number and percentage of Women-Owned Small Medium Enterprises (SMEs) in Malaysia can be seen. Although the involvement of women in entrepreneurship can be classified as active, the failure rate among bumi putera women entrepreneurs are high. Due to that, there is an urgent need to implement this study, and to create better understanding of potential factors to ensure more entrepreneurs emerge successful. Therefore, by adopting the theory of action regulation (ART) which calls for a degree of attention from entrepreneurship perspectives, this study aims to determine the factors influencing entrepreneurial success. Several definitions have been identified from previous studies to better understand the meaning of entrepreneurial success. This study is based on data obtained from questionnaires administered involving 378 women entrepreneurs in Selangor. The data collected were analyzed and evaluated to determine the active performance factors influencing the success of bumiputra women entrepreneurs in Selangor. The analysis revealed that the first independent variable, active action planning, contributed the most to the to dependent variable, entrepreneurial success. The findings of this study also suggested a holistic strategic approach to be framed in order to ensure the success rate among bumi putera women entrepreneurs increases.